Production of extracellular enzymes by fungi associated to the decomposition of plant materials in streams / Produção de enzimas extracelulares por fungos associados à decomposição materiais vegetais em riachos - Silva, Jéssica Barros Aguiar; Universidade Federal do Tocantins (2015)
Fungal cellulases and xylanases derived from the huge degradative capabilities of these microorganisms and excreted to medium, raise a biotechnologixcal interest due to large application potential. The objective of this paper is to identify the production of the enzymes cellulase and xylanase by filamentous fungi isolated from allochthonous leaf litter in a stream in Cerrado ecosystem. The tests were carried out using 100 strains grown in synthetic culture medium containing carboxymethyl cellulose or beechwood xylan as sole carbon source for cellulase and xylanase production detection respectively. Inocula were performed in the center of plates and stored for 4 days at 28 ° C and subjected afterwards to thermal shock at 50 ° C for 16 hours. Plates were stained with Congo red solution and washed with a NaCl solution for betterdetection of the hydrolysis halo. Sixty nine percent of the fungal strains tested were positive for cellulase of which 23% were considered with potential for application in biotechnology. None of the fungal strains was able to degrade xylan